Russia's Imperial Endeavor and Its Geopolitical Consequences The Russia-Ukraine War, Volume Two - Madlovics, Bálint; Magyar, Bálint (Central European University Press, 2023)
Aside from the near-complete devastation of a sovereign state and reversal of the global balance of power, the Russian invasion of Ukraine in 2022 is leading to a radical transformation in the Eastern European and Eurasian regions - including Russia itself. The 12 chapters in this volume examine the main geopolitical consequences of the resurgent imperialist aspirations of the Russian Federation. They examine the ideological tools of history falsification as an integral part of hybrid warfare. Turning to the economy, the book discusses how the war and economic sanctions imposed on Russia are redrawing the geopolitical map and how economic relations would change following a regime transformation. The book discusses the reactions of members of the international community to the invasion, whether threatened or neutral parties or allies. The collection therefore offers a comprehensive picture of the main consequences of the resurgent imperialist aspirations of the Russian Federation. Equipped with the conceptual tools of the analysis with a focus on the patronal features of the political-economic system, the book considers the aftermath of the war. This collection complements the book entitled Ukraine. Patronal Democracy and the Russian Invasion.